Peritoneal MRI in patients undergoing cytoreductive surgery and HIPEC: History, clinical applications, and implementation. Issue 1 (January 2021) - Low, Russell N.; Barone, Robert M.; Rousset, Pascal
Abstract: MR imaging provides considerable advantages in the evaluation of patients with peritoneal metastases. A standardized peritoneal MRI protocol, including diffusion-weighted and gadolinium-enhanced sequences, allows an efficient exploration of small peritoneal tumors that are often missed on other imaging tests. In experienced hands, a dedicated reading allows producing a quantitative and qualitative evaluation of lesional localization to better assist surgeons in the selection of candidates for curative surgery by evaluating the possibility of complete resection, and to plan the surgical procedure. Based on a close collaboration between oncologic surgeon and radiologist, MRI provides a powerful tool for accurate preoperative imaging in patients being considered for curative surgery but also in their surveillance to detect an early recurrence.